Integrating spatial aspects in forest planning: Optimizing boreal forest landscapes reveals trade-offs between timber and grouse habitats at multiple scales - Mazziotta, Adriano; Mykkänen, Reijo; Forsman, Jukka; Kangas, Annika; Lindén, Andreas; Melin, Markus; Eyvindson, Kyle (Elsevier, 2025)
Integrating spatial aspects in forest planning is essential to account for management effects across scales. Forest management impacts wildlife habitat quality by reducing key reproductive resources, posing challenges for balancing timber production with habitat conservation. Because forest species respond to habitat features at multiple spatial scales, the impact of management on habitat quality also varies across scales but remains poorly understood. In this study we evaluate how trade-offs between timber yield and habitat availability vary across species with different habitat needs and spatial scales. We simulated and optimized three boreal Finnish production landscapes spanning a gradient of management intensities using the MELA2.0 forest simulation package. Production possibility frontiers revealed trade-off between economic value (Net Present Value (NPV) of timber) and ecological value (grouse occupancy). Occupancy was modelled for four forest grouse species (hazel grouse, black grouse, capercaillie and willow grouse) using nationwide wildlife triangle census data and predictors related to forest structure and composition at biologically relevant scales: local (stand, ∼0.05 km), home-range (1 km) and landscape (5 km). A 1 % reduction in NPV increased occupancy on average by 7 % at the stand, 9 % at the home-range, and 26 % at the landscape scale. While patterns at smaller scales often mirrored broader trends, discrepancies in certain species-scale combinations highlighted the risk of mismanagement. Habitat quality peaked under conservation-oriented management, NPV under intensive forestry, while compromise solutions emerged from balanced management. The variation in trade-offs at different scales underscores the need for tailored, multi-scale planning to align economic and ecological objectives.
Keywords: trade-off; spatial scale; grouse; optimization; forest planning